Siderophore activity of pyoverdin for Pseudomonas aeruginosa - Charles D. Cox; Peter G. Adams (1985)
Pseudomonas aeruginosa produces an extracellular compound with yellowish green fluorescence, called pyoverdin, which functions as a siderophore. The production of pyoverdin, formerly called fluorescein, is concomitant with the production of another siderophore, pyochelin. Pyoverdin is produced by P. aeruginosa in several forms, some of which were separated on gel filtration columns and on reverse-phase, high-pressure liquid chromatography columns. An active form of iron-free pyoverdin was purified to homogeneity. The elution of pyoverdin from the columns was monitored for absorbance, fluorescence, and siderophore activities. These activities, iron binding, and the stimulation of bacterial iron transport indicated that pyoverdin can function as a siderophore for P. aeruginosa. The siderophore function of pyoverdin may be related to the pathogenicity of this bacterium because pyoverdin stimulated growth not only in iron-deficient culture medium, but also in defined medium containing transferrin and in human serum or plasma.